2010
DOI: 10.4028/www.scientific.net/kem.436.131
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Sintering and Melting of Titanium Powder for Low-Cost Processing

Abstract: The emerging reduction technologies for titanium from ore produce powder instead of sponge. Conventional methods for sintering and melting of titanium powder are costly, as they are energy intensive and require high vacuum, 10-6 Torr or better, since titanium acts as a getter for oxygen at high temperature, adversely affecting mechanical properties. Other melting processes such as plasma arcs have the additional problem of electrode consumption, and direct induction heating of the titanium powder is problemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…[20] Fortunately, the use of MW susceptors such as SiC can significantly enhance the heating efficacy. [21][22][23][24][25] Three mechanisms have been proposed to account for the effectiveness: heat radiation from the MW susceptors at low temperatures, the transformation of the MW-inert TiO 2 film on each Ti powder particle to oxygen-deficient MW-absorbing Ti oxides, and the volumetric heating of Ti powder particles by eddy currents. [25] However, the consistency and capabilities of MW heating of titanium powder remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Fortunately, the use of MW susceptors such as SiC can significantly enhance the heating efficacy. [21][22][23][24][25] Three mechanisms have been proposed to account for the effectiveness: heat radiation from the MW susceptors at low temperatures, the transformation of the MW-inert TiO 2 film on each Ti powder particle to oxygen-deficient MW-absorbing Ti oxides, and the volumetric heating of Ti powder particles by eddy currents. [25] However, the consistency and capabilities of MW heating of titanium powder remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the heating of Ti by microwaves tends to be erratic [229]. For this reason, several studies have utilised microwave susceptors, such as SiC sample holders, to produce predictable and consistent heating of Ti powders [218][219][220]222,[224][225][226]. It has also been reported that TiH 2 is capable of being heated by microwave radiation without susceptors [230,231] to produce small CP-Ti samples with improved density and mechanical properties compared to those produced from metallic Ti powder [228].…”
Section: Microwave Sinteringmentioning
confidence: 99%
“…There have been several studies on the heating susceptibility of Ti powders to microwave radiation [215][216][217][218][219], the densification and microstructure of microwave-sintered Ti [218][219][220][221][222][223][224][225][226][227][228], and the resulting mechanical properties [218,220]. However, the heating of Ti by microwaves tends to be erratic [229].…”
Section: Microwave Sinteringmentioning
confidence: 99%
“…Early research on MWS of metal powders such as Cu, Al, Fe and Co are available [4][5][6]. Recently research was also found on MWS of Ti, TiH2 and pre-alloyed Ti6Al4V powders [7][8][9][10][11][12][13]. These works made a significant contribution in improving the MW furnace design, which increased the sintering efficiency and consequently proved the advantages of MWS metallic materials, such as shorter processing time, enhanced densification and improved mechanical properties.…”
Section: Introductionmentioning
confidence: 99%